Socially responsible medical education: innovations and challenges in a minority setting - Schofield, Aurel; Bourgeois, Daniel (Medical Education, 2010)
Context Distributed medical education sites help train, recruit and retain doctors, notably in rural and isolated areas, by providing education and training in these areas and adapting their curriculum to meet the host community’s health needs. Objectives The Centre de Formation Médicale du Nouveau Brunswick (CFMNB; New Brunswick Medical Education Centre) was established by a partnership between two academic institutions, the Université de Sherbrooke (University of Sherbrooke), situated in the province of Quebec, and the Université de Moncton (University of Moncton), situated in the province of New Brunswick, in Canada. The CFMNB is specifically targeting a minority community (Acadians). Working to establish a high‐quality medical education programme, the CFMNB has also set community objectives to meet not only the health needs of this population, but also its social and economic needs. Methods This paper describes the overall objectives of this project, which are: to reduce the gap between community needs and academic institutional needs; to address ethno‐cultural and language differences in a defined minority population, and to develop collaboration between the partners involved, including government and community entities which are often perceived as operating in isolation from one another. We also describe why and how the CFMNB developed community‐focused objectives and the challenges that came with these innovations, and present lessons from the experience that may be relevant to other sites interested in the social responsibility of medical schools. Conclusions The CFMNB has produced interesting work and innovations in the field of social responsibility and has encountered many challenges. Continuing interaction between medical education, health research and health services to better address the needs of the population has been established. The information obtained by this process has been used to build a strategic plan for the CFMNB in order to ensure that it is socially responsive and has significant generalisable features.

Canadian medical schools addressing Francophone minority needs - Schofield, Aurel; Bardeau-Rodigue, Danielle; Leblanc, P. (Social Innovations Journal, 2019)

Improving the recruitment and retention of doctors by training medical students locally - Landry, Michel; Schofield, Aurel; Bordage, Rachel; Bélanger, Mathieu (Medical Education, 2011)
Context The global shortage of doctors is of concern. This is particularly true in French‐speaking regions of New Brunswick, Canada, where there is no medical school. Since 1981, francophone medical students from New Brunswick have been able to undertake part of their training in their province through an agreement with medical schools in another province. We studied the effects of frequency and length of exposure to the province of origin during medical training on the likelihood that a doctor will ever or currently practise medicine in that province. Methods A questionnaire was sent to 390 francophone doctors from New Brunswick to collect information on history of medical training and practice. Multivariate logistic regressions were used to identify whether exposure to New Brunswick during medical training at the undergraduate and postgraduate levels affects the likelihood of ever or currently practising in the province. Results A total of 263 doctors participated. Among family doctors, those with exposure to their province of origin in 1, 2, 3 or 4 years of undergraduate training were 2.5 (95% confidence interval [CI] 0.8–7.4), 2.5 (95% CI 0.7–8.6), 9.3 (95% CI 1.5–56.9) and 9.3 (95% CI 1.4–60.1) times more likely, respectively, to currently practise in New Brunswick than doctors who had experienced no exposure to the province during undergraduate training. Among specialty doctors, exposure to New Brunswick during undergraduate training had no effect on location of practice. Family and specialty doctors who had been exposed to New Brunswick during postgraduate residency were 5.9 (95% CI 2.3–14.9) and 3.2 (95% CI 0.9–11.6) times more likely, respectively, to practise in the province than doctors without postgraduate exposure. Conclusions Greater exposure to New Brunswick during medical training is associated with significantly better odds that doctors will be recruited to and retained in the province. Some effects are perceived for exposure during both undergraduate (most importantly in the final years) and postgraduate programmes.

Recruiting doctors from and for underserved groups: Does New Brunswick's initiative to recruit doctors for its linguistic minority help rural communities? - Beauchamp, Jacinthe; Bélanger, Mathieu; Schofield, Aurel; Bordage, Rachel; Donovan, Denise; Landry, Michel (Canadian Journal of Public Health / Revue canadienne de santé publique, 2013)
Objectives Within health care, there are underserved groups. New Brunswick’s French-speaking minority, which also mostly lives in rural communities, is one such group. A physician shortage potentially prevents this population from accessing health promotion and clinical prevention services. This study analyzes whether New Brunswick Francophone doctors with rural backgrounds are more likely than doctors from urban regions to set up practice in rural communities of the province. Methods A questionnaire was sent to 390 New Brunswick Francophone physicians admitted in medicine between 1973 and 2000. It collected information on geographic origin and history of medical practice. Multivariate logistic regressions were used to identify whether a rural background is associated with the likelihood of ever and currently practicing in rural communities. We used the General Practice Rurality Index-simplified to quantify the rurality level of communities. Results In total, 264 (67%) physicians participated. A rural background was positively associated with the establishment of a first medical practice in a rural community. This relationship was only significant among family physicians. There was no statistically significant relationship between rurality of community of origin and rurality of current community of practice among either family or specialty physicians. Conclusion Although Francophone doctors with a rural background were more likely than their urban counterparts to set up their first practice in a rural community, this effect was not sustained. This raises questions as to why they leave rural communities and highlights the importance of measures to retain doctors as a way to promote public health for underserved rural groups.

Perceived Health status of Francophones and Anglophones in an official bilingual Canadian province - Bélanger, Mathieu; Bouchard, Louise; Gaboury, Isabelle; Sonier, Brigitte; Gagnon-Arpin, Isabelle; Schofield, Aurel; Bourque, Paul-Emile (Canadian Journal of Public health, 2011)
Objective: It has been reported that being part of a minority group may be negatively associated with self-perceived health. The objective of this analysis was to determine whether there are differences in perceived health between the Francophone minority and Anglophone majority in New Brunswick, the only officially bilingual province in Canada. Methods: Data from the first four primary cycles of the Canadian Community Health Survey (2001 to 2007) were obtained for 17,729 New Brunswick residents. Odds of reporting good health among Francophones and Anglophones were compared using multivariate logistic regressions accounting for age, health-related behaviours, socio-demographic variables, and medical conditions. Results: In the final models, Francophone men and women were less likely than Anglophones to report their health as being good, although these differences were not statistically significant (Odds ratio, 95% confidence interval: 0.88, 0.61–1.26; 0.71, 0.49-1.04, in men and women, respectively). Conclusion: This study suggests that being part of the linguistic minority in New Brunswick is not associated with statistically significant differences in self-perceived health.